PRECLINICAL STUDIES OF α(1,2)-L-RAMNO-α(1,4)-D-GALACTOPIRANOZILURONAN FROM RHIZOMES ACORUS CALAMUS L. IN CANCER EXPERIMENT - K. A. Lopatina; T. G. Razina; E. P. Zueva; S. G. Krylova; A. M. Guryev; E. N. Amosova; O. Y. Rybalkina; E. A. Safonova; L. A. Efimova; M. V. Belousov (Сибирский онкологический журнал)
α(1,2)-L-ramno-α(1,4)-D-galaktopiranoziluronan from rhizomes Acorus calamus L. administered intravenously enhances the antitumor and antimetastatic efficacy of cyclophosphamide in mice with Lewis lung carcinoma, lung cancer – 67 and melanoma B-16.